The dynamic capability development through learning orientation: Malaysian International New Venture (INV) firms / Afifah Alwani Ramlee - Ramlee, Afifah Alwani (Universiti Teknologi MARA, Kedah, 2019)
Traditional theories of internationalisation have long been questioned because of the fast-changing environment and deregulations. As the time has evolves, the business environment has become more challenging and it started to question the initial proposals of the RBV for being static and neglecting the influence of market dynamism. In particular for International New Venture (INV) firms, namely as a firm whichseeks a significant competitive advantage from the use of their resources in pursuing international sales in multiple countries from the early stages of their operation. It is also a question to ponder on how these small firms could survive in a dynamic environment with a lack of resources and skills. Additionally, INV firms are able to penetrate the international market within a short period of establishment because the firm needs to own unique capabilities to make their resources become more useful. However, several issues surrounding the dynamic capabilities conceptualization remain uncertain. The quick growth of the dynamic capabilities literature and its diversity is disengaged and pointing in different directions. In regard of this situation, there is still a gap in understanding the "link between learning, capability development and firm growth" (Zahra et al., 2009,p.91).